Development of blood and saliva sample preparation workflows for isothermal POC molecular diagnostic assays - Kärkkäinen, Niina-Elina (My University, 2023)
Human cytomegalovirus (CMV) is the leading cause of congenital viral infections in children and the leading non-genetic cause of sensorineural hearing loss. In addition, CMV infection is a significant cause of neurodevelopmental disabilities leading to neonate morbidity and even occasional mortality. Despite CMV’s high prevalence and pathogenicity, standardized approaches and diagnostic tests are lacking for large-scale screening. Loop-mediated isothermal amplification (LAMP) is an emerging amplification technique for nucleic acids, and it has potential applications in point-of-care (POC) diagnostics with high sensitivity and specificity. The aim of this study is to develop sample preparation workflows with various sample types for isothermal point-of-care assays. The assay was conducted with loop-mediated isothermal amplification and optimized with different reaction temperatures, enzyme mixes, and LAMP primers. Sample preparation workflows for CMV spiked blood, urine, and saliva samples were optimized with various incubation conditions, sample dilutions, and red blood cell –depletion protocols. LAMP assay development was done with a quantitative PCR (qPCR) instrument, but the final version of the assay was also assessed with an experimental POC -arrangement and dry LAMP reagents. The assay performance was confirmed to be compatible with qPCR. Limit of detection was determined to be 2000 IU/ml for blood, 1500 IU/ml for saliva, and 1000 IU/ml for urine, demonstrating that the developed isothermal nucleic acid amplification assay is sensitive for POC CMV testing. Furthermore, this study indicates that LAMP is a promising method for analysing difficult sample materials, such as blood and saliva, which are often challenging sample materials for qPCR assays due to inhibitors. These results will aid the future applicability and design of POC –methods for CMV and other target analytes.
Keywords: cytomegalovirus, point-of-care, loop-mediated isothermal amplification, sample preparation, detection, diagnosis